SMEs probability of default: the case of the hospitality sector - Luís Pacheco (Tourism & Management Studies)
In this paper we analyze a set of financial ratios from hospitality sector SMEs in order to ascertain which factors determine a greater probability of default. We choose the hospitality sector due to its importance in the Portuguese economy and has been particularly affected by the recent economic downturn and austerity measures and because, to the best of our knowledge, this sector has never been the object of such a study. Usually the literature seeks to find a set of variables which are significant in the estimation of default and multiple discriminant analysis and logit methodology are the main avenues of research on this area. Our data was collected from SABI and we followed logit methodology. Our results recommend that in ascertaining the creditworthiness of borrowers only debt and equity variables appear to be relevant to explaining failure, and overreliance on profit as an indication of good financial performance should be limited. The main reason for our rather poor results could be from problems with the data quality, possibly since the accounts published by firms aren’t reliable and tend to present negative results.